Effects of growth hormone on cardiac remodeling and soleus muscle in rats with aortic stenosis-induced heart failure - Lima, Aline R.R. [UNESP]; Pagan, Luana U. [UNESP]; Damatto, Ricardo L. [UNESP]; Cezar, Marcelo D.M. [UNESP]; Bonomo, Camila [UNESP]; Gomes, Mariana J. [UNESP]; Martinez, Paula F.; Guizoni, Daniele M. [UNESP]; Campos, Dijon H.S. [UNESP]; Damatto, Felipe C. [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina P. [UNESP] (Impact Journals, 2017)
Background: Skeletal muscle wasting is often observed in heart failure (HF). The growth hormone (GH)/insulin-like growth factor-1 (IGF-1) axis is impaired in HF. In this study, we evaluated the effects of GH on soleus muscle and cardiac remodeling in rats with aortic stenosis (AS)-induced HF. Methods: AS was created by placing a stainless-steel clip on the ascending aorta. After clinically detecting HF, GH (2 mg/kg/day) was subcutaneously injected for 14 days (AS-GH group). Results were compared with those from Sham and non-treated AS groups. Transthoracic echocardiogram was performed before and after treatment. Protein expression was evaluated by Western blot and satellite cells activation by immunofluorescence. Statistical analyzes: ANOVA and Tukey or Kruskal-Wallis and Student-Newman-Keuls. Results: Before treatment both AS groups presented a similar degree of cardiac injury. GH prevented body weight loss and attenuated systolic dysfunction. Soleus cross-sectional fiber areas were lower in both AS groups than Sham (Sham 3,556±447; AS 2,882±422; AS-GH 2,868±591 μm2; p=0.016). GH increased IGF- 1 serum concentration (Sham 938±83; AS 866±116; AS-GH 1167±166 ng/mL; p < 0.0001) and IGF-1 muscle protein expression and activated PI3K protein. Neural cell adhesion molecule (NCAM) immunofluorescence was increased in both AS groups. Catabolism-related intracellular pathways did not differ between groups. Conclusion: Short-term growth hormone attenuates left ventricular systolic dysfunction in rats with aortic stenosis-induced HF. Despite preserving body weight, increasing serum and muscular IGF-1 levels, and stimulating PI3K muscle expression, GH does not modulate soleus muscle trophism, satellite cells activation or intracellular pathways associated with muscle catabolism.
Keywords: Growth hormone; Heart failure; Muscle trophicity; Satellite cells; Skeletal muscle